Diagnostic performance and color overlay pattern in shear wave elastography (SWE) for palpable breast mass. Issue 10 (October 2015) - Park, Jiyoon; Woo, Ok Hee; Shin, Hye Seon; Cho, Kyu Ran; Seo, Bo Kyoung; Kang, Eun Young
Highlights: The mean of Emax, Emean, ESD, and Eratio were higher in malignant lesions. The optimal cut-off value for color pattern was between patterns 2 and 3. Grayscale US combined with color pattern, Emax and Emean improved specificity. Echogenic halo was significantly related to color pattern and pathology. Color pattern represents quantitative SWE with similar diagnostic performances. Abstract: Objective: The purpose of this study is to evaluate the diagnostic performance of SWE in palpable breast mass and to compare with color overlay pattern in SWE with conventional US and quantitative SWE for assessing palpable breast mass. Methods: SWE and conventional breast US were performed in 133 women with 156 palpable breast lesions (81 benign, 75 malignant) between August 2013 to June 2014. Either pathology or periodic imaging surveillance more than 2 years was a reference standard. Existence of previous image was blinded to performing radiologists. US BI-RADS final assessment, qualitative and quantitative SWE measurements were evaluated. Diagnostic performances of grayscale US, SWE and US combined to SWE were calculated and compared. Correlation between pattern classification and quantitative SWE was evaluated. Results: Both color overlay pattern and quantitative SWE improved the specificity of conventional US, from 81.48% to 96.30% ( p = 0.0005), without improvement in sensitivity. Color overlay pattern was significantly related to all quantitative SWE parameters and malignancy rate ( p <0.0001.). The optimal cutoff of color overlay pattern was between 2 and 3. Emax with optimal cutoff at 45.1 kPa showed the highest Az value, sensitivity, specificity and accuracy among other quantitative SWE parameters ( p <0.0001). Echogenic halo on grayscale US showed significant correlation with color overlay pattern and pathology ( p < 0.0001). Conclusions: In evaluation of palpable breast mass, conventional US combine to SWE improves specificity and reduces the number of biopsies that ultimately yield a benign result. Color overlay pattern classification is more quick and easy and may represent quantitative SWE measurements with similar diagnostic performances.